Digital Preservation of Balinese Heritage through Educational Game: A Case Study of Perang Pandan Tradition - Komang Redy Winatha; Ni Kadek Nita Noviani Pande; Ni Kadek Dwi Dina Oktaviani (Jurnal Krisnadana, 2026)
Tradition is a series of long-established customs that have been continuously practiced, playing a significant role in the life of a community within a country, culture, time period, or religion. The Perang Pandan tradition is one of the unique cultural heritages of Tenganan Pegringsingan Village, Bali, embodying values of bravery and reverence for Lord Indra. This study aims to develop an Android-based Perang Pandan game by implementing the Finite State Machine (FSM) method to systematically manage character behavior and game mechanics. FSM was chosen for its advantages in controlling transitions between states—such as attacking, defending, and moving—creating an interactive and realistic gameplay experience. The game development process followed several stages: analysis, design, implementation, and testing. Black-box testing results indicate that the game runs smoothly on Android devices and successfully conveys traditional elements through engaging visuals and gameplay. Additionally, the User Experience Questionnaire (UEQ) testing revealed high scores in attractiveness, ease of use, and efficiency, highlighting the game's effectiveness in providing an enjoyable and educational experience.